Factors Related to Reporting and Recording of Work Accidents at Mental Hospital X in Semarang City (Jurnal Penelitian dan Pengembangan Kesehatan Masyarakat Indonesia, 2022)
Background: very hospital has an obligation to carry out recording and reporting activities for work accidents that have been connected to the hospital management information system. The purpose of this study was to determine the factors related to reporting and recording work accidents in Mental Hospital X Methods: this type of research is quantitative with a descriptive approach, using a cross-sectional method with a simple random sampling technique totaling 72 respondents. The instrument used is a questionnaire. Data analyzed using chi-square test. Results: the results of this study revealed that variables related to reporting and recording work accidents are staffing status (p = 0.01) and training history (0.002). While the unrelated variables are age (0.129), education level (0.813), knowledge level (0.233), and length of service (0.722). Conclusion There are 2 variables related to reporting and recording work accidents, namely staffing status and training history. And there are 4 variables that are not related to reporting and recording work accidents, namely age, education level, level of knowledge, and length of service. Keywords: Reporting, Recording, and Work Accidents